Materials research innovations (Springer, 1997)
Includes papers in all core areas of materials research: metals, polymers, ceramics, composites, electronic materials, and biomaterials. They may be experimental or theoretical and should report on: synthesis of new phases or composites, new processes for making new phases faster, cheaper, "greener", new characterization tools and their application, new devices based on new materials and, new theories or correlations to explain observations.